Brewing microbiology : current research, omics and microbial ecology - Bokulich, Nicholas A.; Bamforth, Charles W., 1952- (Caister Academic Press, 2017)
Highly recommended for anyone involved in the microbiology of brewing, this volume surveys the most recent discoveries in brewing microbiology, with an emphasis on omics techniques and other modern technologies. Discoveries in these areas have furthered our knowledge of brewing processes, with practical applications from barley growth and malting to yeast management, strain selection, fermentation control, and quality assurance. The chapters, written by experts in the field, aim not only to illuminate recent progress, but also to discuss its impact on brewing practices. Topics covered include the physiology, fermentation, taxonomy, diversity, typing, genetic manipulation, genomics and evolution of brewing yeasts. Further areas covered include the fungal contamination of barley and malt, spoilage by lactic acid bacteria and gram-negative bacteria, and beer-spoiling yeasts.